Muscle: Ischemia, Infarction, and Compartment Syndrome - Broski, Stephen M.; Tiegs Heiden, Christin A.; Ringler, Michael D. (Seminars in Musculoskeletal Radiology, 2017)
Muscle ischemia and infarction are associated with a variety of pathologic conditions and commonly encountered in busy imaging practices. This article reviews the most common clinical scenarios in which they are seen including compartment syndrome, diabetic myonecrosis, and rhabdomyolysis, focusing on the imaging findings and differential diagnosis for each disease process. Magnetic resonance imaging is increasingly useful in differentiating myonecrosis from muscle ischemia and myositis, and it is highly accurate in diagnosing the most common type of compartment syndrome.
Keywords: Compartment Syndrome; muscle ischemia; myonecrosis; muscle infarct